2016
DOI: 10.1021/acs.bioconjchem.6b00260
|View full text |Cite
|
Sign up to set email alerts
|

Coordinative Amphiphiles as Tunable siRNA Transporters

Abstract: In this study, we developed coordinative amphiphiles for use as novel siRNA transporters. As a modification of a conventional cationic lipid structure, we replaced the cationic head with zinc(II)-dipicolylamine complex (Zn/DPA) as a phosphate-directing group, and used various membrane-directing groups in the place of the hydrophobic tails. These simple amphiphiles are readily synthesized and easy to modify. The Zn/DPA head groups bind to the phosphate backbones of siRNAs, and to our surprise, they prevented th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…[44] E. K. Bang and co-workers have reported an effective delivery of siRNA by synthesized low toxicity cationic head with zinc(II)-dipicolylamine complex (Zn-DPA) (as a phosphate directing group) which used different membrane-directing groups in the place of water-hating species (hydrophobic tails) i. e., group-oleoyl (17 a), pyrenebutyryl (17 b), and biotin (17 c) ( Figure 10). [45] While, in vitro evaluation of transfection efficiency against HepG2, HeLa and HCT116 (human colon cancer) cell-lines, they have observed that 17 b and 17 c were the best in delivering siRNAs into the cells. Whereas, 17 c which is a simple biotin-tethered molecule, that allowed specific delivery towards the biotin receptor-rich cancer cells.…”
Section: Zinc(ii) Mediated Sirna Deliverymentioning
confidence: 99%
“…[44] E. K. Bang and co-workers have reported an effective delivery of siRNA by synthesized low toxicity cationic head with zinc(II)-dipicolylamine complex (Zn-DPA) (as a phosphate directing group) which used different membrane-directing groups in the place of water-hating species (hydrophobic tails) i. e., group-oleoyl (17 a), pyrenebutyryl (17 b), and biotin (17 c) ( Figure 10). [45] While, in vitro evaluation of transfection efficiency against HepG2, HeLa and HCT116 (human colon cancer) cell-lines, they have observed that 17 b and 17 c were the best in delivering siRNAs into the cells. Whereas, 17 c which is a simple biotin-tethered molecule, that allowed specific delivery towards the biotin receptor-rich cancer cells.…”
Section: Zinc(ii) Mediated Sirna Deliverymentioning
confidence: 99%
“…In fact, dpa-metal complexes are well-known for their recognition of phosphoric acid derivatives, including ATP. [11][12][13][14][15][16] CyDs are well-known water-soluble host molecules comprising nano-sized hydrophobic cavities that enable them to incorporate various organic compounds in aqueous solutions. 17 In addition, the structural modications of CyDs are straightforward, which allow the incorporation of a variety of functionalities for modulating their properties.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the adjuvant effects of ssRNAs derived from the cricket paralysis virus (CrPV) intergenic region (IGR) internal ribosome entry site (IRES) . Here, we studied the adjuvant effect of these ssRNAs formulated with coordinative amphiphiles (CAs) …”
Section: Introductionmentioning
confidence: 99%
“…A CA is defined as an amphiphilic molecule consisting of a phosphate‐directing group [a phosphate‐specific binder, zinc‐dipicolylamine (Zn/DPA) complex] and a membrane‐directing group . It serves as a cationic lipid mimic, which are amphiphiles with positively charged heads and are commonly used as nonviral vectors for nucleic acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation